Phenolic Class Analysis in Honey: Comparison of Classical and Single UV Spectrum Methodologies - Paula, Vanessa B. (2024)
The analytical results from a study of 16 honey samples (extra white to dark honey color range) of phenolic compounds obtained using the single UV spectrum methodology and classical spectrophotometric methods (Folin–Ciocalteu and AlCl3 methods) are presented. The first method quantified all classes of phenolic compounds in honey’s SPE-C18 extract: the total hydroxybenzoic acid content (concentrations between 0.37 ± 0.05 and 4.46 ± 0.37 mg of gallic acid/g of honey), total hydroxycinnamic acid content (0.13 ± 0.03 and 2.76 ± 0.13 mg of ferulic acid/g of honey), and total flavonoid content (0.15 ± 0.03 and 1.63 ± 0.17 mg of quercetin/g of honey). The total phenolic contents were, on average, 1.86 ± 0.72 and 1.78 ± 0.79 times higher than the results obtained for raw honey and the SPE-C18 extract, respectively, using the classical Folin–Ciocalteu method. The total flavonoid contents, on average, were 6.02 ± 3.14 times larger and 0.66 ± 0.33 times smaller than the results obtained using the classical AlCl3 method for raw honey and SPE-C18 extract, respectively.